2021
DOI: 10.2147/copd.s324467
|View full text |Cite
|
Sign up to set email alerts
|

TRONARTO: A Randomized, Placebo-Controlled Study of Tiotropium/Olodaterol Delivered via Soft Mist Inhaler in COPD Patients Stratified by Peak Inspiratory Flow

Abstract: Background: Inhaled bronchodilator therapy is currently the mainstay of treatment for patients with chronic obstructive pulmonary disease (COPD). Some inhalers require patients to achieve certain inhalation efforts either to activate the device or to deliver medication to the site of action. For dry powder inhalers, low peak inspiratory flow (PIF) can result in poor medication delivery but the clinical significance of this is not well understood. Methods: TRONARTO was a 4-week, randomized, double-blind, placeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…As such, fine particle fraction is a key determinant of the proportion of the emitted dose delivered to the lungs. It has been confirmed both in vivo and in vitro that the Respimat SMI provides high lung deposition and low oropharyngeal deposition of drug particles compared with pMDIs and DPIs [ 12 , 29 31 ], and clinically, lung function outcomes are consistent irrespective of the peak inspiratory flow a patient can generate [ 32 ]. There is also evidence that the Respimat SMI is able to deliver a higher dose to the lungs compared with DPIs and pMDIs, irrespective of inhaler position, which is important when patients do not follow instructions regarding correct inhaler orientation [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…As such, fine particle fraction is a key determinant of the proportion of the emitted dose delivered to the lungs. It has been confirmed both in vivo and in vitro that the Respimat SMI provides high lung deposition and low oropharyngeal deposition of drug particles compared with pMDIs and DPIs [ 12 , 29 31 ], and clinically, lung function outcomes are consistent irrespective of the peak inspiratory flow a patient can generate [ 32 ]. There is also evidence that the Respimat SMI is able to deliver a higher dose to the lungs compared with DPIs and pMDIs, irrespective of inhaler position, which is important when patients do not follow instructions regarding correct inhaler orientation [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The TRONARTO study evaluated the efficacy of drug delivery via the SMI in patients with COPD and different inhalation abilities. 17 TRONARTO (NCT04223843) was a Phase IV, randomized, double-blind, placebo-controlled, multicenter, parallel-group study that investigated the efficacy of tiotropium/olodaterol (TIO/OLO) 5 μg/5 μg delivered via the SMI, Respimat ® (Boehringer Ingelheim, Ingelheim am Rhein, Germany), on lung function in patients with COPD stratified by inhalation ability (<60 L/min or ≥60 L/min), measured with the In-Check DIAL G16 (Clement Clarke Ltd, Harlow, UK) set at medium-low resistance. 17 Included patients were aged ≥40 years, current or ex-smokers, with a spirometry-confirmed diagnosis of moderate-to-severe COPD.…”
Section: Introductionmentioning
confidence: 99%
“… 17 TRONARTO (NCT04223843) was a Phase IV, randomized, double-blind, placebo-controlled, multicenter, parallel-group study that investigated the efficacy of tiotropium/olodaterol (TIO/OLO) 5 μg/5 μg delivered via the SMI, Respimat ® (Boehringer Ingelheim, Ingelheim am Rhein, Germany), on lung function in patients with COPD stratified by inhalation ability (<60 L/min or ≥60 L/min), measured with the In-Check DIAL G16 (Clement Clarke Ltd, Harlow, UK) set at medium-low resistance. 17 Included patients were aged ≥40 years, current or ex-smokers, with a spirometry-confirmed diagnosis of moderate-to-severe COPD. 17 The TRONARTO study (n=213) showed that treatment with TIO/OLO via the SMI results in significant lung function improvements versus placebo, irrespective of the PIF that a patient can generate.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations